Comparison of Patient-Reported Outcomes After Suprapatellar Versus Infrapatellar Nailing Techniques for Tibial Shaft Fractures: A Systematic Review and Meta-analysis. Issue 6 (June 2022) - Sepehri, Aresh; You, Daniel; Lobo, Akshay A.; Schneider, Prism; Lefaivre, Kelly A.; Guy, Pierre
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To compare patient-reported outcome measures (PROMs) between patients who underwent intramedullary nail (IMN) fixation for tibial shaft fractures using an infrapatellar (IP) or the newer suprapatellar (SP) approach. Secondary outcomes included fluoroscopic radiation exposure, operative time, and radiographic outcomes. Data Sources: A systematic literature search of the databases Ovid MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials Study Selection. Study Selection: Level I to III studies in which patients over the age of 18 years with acute tibial shaft fractures who underwent tibial IMN fixation using an IP or SP approach for fracture fixation were assessed for inclusion. Studies with a minimum of 10 patients in each cohort that reported on postoperative patient-reported outcomes with at least 6 months of follow-up were included for analysis. Data Extraction and Synthesis: Twelve studies that reported PROMs and compared IP and SP intramedullary nailing of tibial shaft fractures were analyzed. This included 654 patients who underwent IP IMN fixation and 542 patients who underwent SP IMN fixation. A random-effects model for unadjusted/crude study estimates were pooled using inverse variance (IV) weighting for continuous variable analysis. Conclusions: This review found a significant improvement in PROM for patients with tibial shaft fractures when the SP IMN technique was used. In addition, there was a significant decrease in intraoperative fluoroscopy time consistent with other radiographic findings demonstrating improved start point accuracy and reduction with SP IMN fixation of tibial shaft fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.